Petro Gulak-Artemovsky and Kharkiv University - Домановська, Марина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The paper deals with the teaching and administrative activities of Petro Gulak-Artemovsky. In the period 1818–1849 in Kharkiv University he taught courses on the Polish language, Russian history, geography and statistics, and also was rector (1841–1849). Attention is paid to the formation of his socio-political views: on the one hand, high posts and titles conditioned his complete dependence on imperial ideology, on the other hand, his poetic work as a component of the «new Ukrainian literature» brought him to the process of Ukrainian national revival, in which he took a prominent place.